Metode Therapeutic Lifestyle Changes untuk Manajemen Berat Badan - Mulyati, Sri (PT. Kalbe Farma Tbk., 2015)
Makin meningkatnya prevalensi obesitas dan penyakit degeneratif terkait obesitas di Indonesia, menjadikan obesitas sebagai masalah kesehatan penting yang menantang setiap praktisi kesehatan untuk memilih manajemen berat badan yang tepat. Therapeutic Lifestyle Changes (TLC) direkomendasikan oleh berbagai organisasi kesehatan sebagai strategi terapi bagi individu dengan obesitas yang berisiko diabetes tipe 2 dan/atau penyakit jantung koroner. TLC mengedepankan healthy eating plan, weight management, dan physical activity.The prevalence of obesity and associated degenerative diseases in Indonesia is increasing. Our society as well as health care practitioners, should treat obesity comprehensively as a healthcare problem. The challenge is to select an approriate weight management therapy. Therapeutic Lifestyle Changes (TLC) is recommended by various health organizations as therapeutic strategy for obese persons who is at risk for type 2 diabetes and/or coronary heart disease. TLC focuses on healthy eating plan, weight management, dan physical activity.